Measles, Malnutrition and Mortality: Puerto Rico, 1917-1918 - Rigau-Pérez, José G.; Vallejo-Calzada, Evelyn D. (Puerto Rico Health Sciences Journal, 2020)
Objective: Recent measles outbreaks in the United States and Europe have highlighted the threat of the disease. We studied the 1917-1918 epidemic in Puerto Rico to better understand the social and place-specific risk factors and severity of such crises. Methods: We reviewed medical and government reports, newspapers and private contemporary documents. Results: The epidemic developed over two years, encompassed the Island, and caused nearly 2,000 deaths among more than 9,000 registered cases (with much underreporting). During the first six months, 59% of fatalities were children under 2 years of age. Officials recognized poor nutrition and living conditions as an important determinant of epidemic severity. Responses came from different social sectors before the central government mobilized to help. In San Juan, Catholic and Protestant churches and philanthropic women from both Spanish and Englishlanguage communities joined to provide free milk to needy children and create a temporary Infants’ Hospital. Despite food scarcity and wartime conditions, central and municipal governments established hospitals and milk stations. Conclusion: Studies that examine the impact of reemerging diseases in a time and place-specific context look at disease severity together with the socioeconomic conditions of patients and health care systems. This type of investigation also suggests avenues into the history of pediatrics, the use of epidemiologic methods, the utility of historical statistics, nutritional history, and the history of disaster response. Historical and recent outbreaks show the need for health care professionals and public health systems to be prepared to confront measles epidemics.